2007
DOI: 10.1007/s00704-006-0281-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distributions of heating, cooling, and industrial degree-days in Turkey

Abstract: SummaryThe degree-day method is commonly used to estimate energy consumption for heating and cooling in residential, commercial and industrial buildings, as well as in green houses, livestock facilities, storage facilities and ware houses. This article presents monthly and yearly averages and spatial distributions of heating, cooling, and industrial degree-days at the base temperatures of 18 � C and 20 � C, 18 � C and 24 � C, and 7 � C and 13 � C, respectively; as well as the corresponding number of days in Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…GDD are also commonly used in other fields, such as forestry (Ruosch et al, ), vegetation conditions (Miller et al, ; Graham et al, ), and pest management (Pruess, ). In more recent years, however, many studies have focussed on the use of HDD and CDD to estimate annual and seasonal trends in the energy demand for heating and cooling residential, commercial, and industrial buildings, especially in the context of climate change (Hadley et al, ; Yildiz and Sosaoglu, ; Morna and van Vuuren, ; Wang et al, ; Zhao and Magoulès, ; Auffhammer and Mansur, ; Wang and Chen, ; Labriet et al, ; Shi et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GDD are also commonly used in other fields, such as forestry (Ruosch et al, ), vegetation conditions (Miller et al, ; Graham et al, ), and pest management (Pruess, ). In more recent years, however, many studies have focussed on the use of HDD and CDD to estimate annual and seasonal trends in the energy demand for heating and cooling residential, commercial, and industrial buildings, especially in the context of climate change (Hadley et al, ; Yildiz and Sosaoglu, ; Morna and van Vuuren, ; Wang et al, ; Zhao and Magoulès, ; Auffhammer and Mansur, ; Wang and Chen, ; Labriet et al, ; Shi et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Although the respective increase and decrease generally followed the corresponding temperature trends and noticeably depended on latitude, that study also accounted for the spatial patterns over Europe, which may be a key factor for regional impacts, as reported for different countries (e.g. Christenson et al, ; Yildiz and Sosaoglu, ; Semmler et al, ; De Rosa et al, ; Cvitan and Sokol Jurković, ).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, it would be more appropriate to use a lower value of CDD for northern climates, where the thermal protection and the air tightness of the building envelope are generally increased, allowing for less heat flows between the interior and the ambient environment. Consequently, with the aim of covering all geographical area of Europe and taking into account ASHRAE recommendations, the base temperature for both cooling and heating was considered equal to 18 °C [17,20,21].…”
Section: Methodology For Establishing Climatic Zonesmentioning
confidence: 99%
“…The value of heating degree day (HDD) has been widely used as an index of quantity of heating energy consumption for buildings in different locations (Thom, , ; Quayle and Diaz, ). Many studies have investigated the effects of climate change on HDD elsewhere (Kadioğlu et al , ; Frank, ; Christenson et al , ; Yildiz and Sosaoglu, ; Jiang et al , ; Semmler et al , ; Rehman et al , ; Mourshed, ; Castañeda and Claus, ; You et al , ; De Rosa et al , ; Spinoni et al , ), but there are few related studies reported for China. In addition to the amount of heating energy consumption for warming buildings during the heating period, the prices for heating energy are also determined by the heating duration (length of the heating period (HL)).…”
Section: Introductionmentioning
confidence: 99%
“…The value of heating degree day (HDD) has been widely used as an index of quantity of heating energy consumption for buildings in different locations (Thom, 1952(Thom, , 1954Quayle and Diaz, 1980). Many studies have investigated the effects of climate change on HDD elsewhere (Kadioglu et al, 2001;Frank, 2005;Christenson et al, 2006;Yildiz and Sosaoglu, 2007;Jiang et al, 2009;Semmler et al, 2010;Rehman et al, 2011;Mourshed, * Correspondence: X.-J Shen, Northeast Institute of Geography and Agroecology, Chinese Academy of Sciences, 4888 Shengbei Street, Changchun 130102, P. R. China. E-mail: shenxiangjin@iga.ac.cn 2012; Castañeda and Claus, 2013;You et al, 2014;De Rosa et al, 2015;Spinoni et al, 2015), but there are few related studies reported for China.…”
Section: Introductionmentioning
confidence: 99%